Cognitive style as a correlate of senior school students achievement in physics in Sokoto State, Nigeria - Afees Akanni Amuda; Abdulrasaq Oladimeji Akanbi (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This study examined cognitive style as a correlate of senior secondary school students’ achievement in physics in Sokoto State, Nigeria. This study adopted ex post facto research of the co-relational type. The population for the study was S. S. II students’ in Sokoto State. The sample consisted of seven hundred and thirty-one (731) senior secondary school students (SSS II) offering physics proportionately selected from senior secondary schools across the three senatorial districts in Sokoto State, Nigeria. Research instruments employed to elicit data for the study were the Students’ Cognitive style Inventory (SCSI), and Physics Achievement Test (PAT). Pearson-product moment correlation coefficients (PPMC), Fishers’ transformation (Z-test) statistic were employed to analyse data at .05 level of significance. The results revealed that there was no significant relationship between students’ cognitive style and their achievement in physics; there was no statistically significant difference in the strength of correlation between students’ cognitive style and their achievement in physics, based on gender amongst others. It was recommended that students should be trained on cognitive style to be able to predict correctly their achievement in physics.